Comparison Of Fuzzy Time Series Chen and Fuzzy Time Series Markov Chain Methods in Forecasting Consumer Price Index in Banda Aceh - Syahrini, Intan; Tamimi, Afifah; Zuhra, Rahma; Amri, Saiful; Oktavia, Rini (Syiah Kuala University, 2025)
The Consumer Price Index (CPI) is utilized to determine a country's inflation and deflation rate. Inflation decreases the buying power of consumers; meanwhile, continuous deflation will lead to a recession. characterized by a stagnant economy and a diminished willingness among manufacturers to innovate. The CPI trends serve as a valuable economic indicator and a standard for manufacturing costs that reflect price fluctuations at the consumer level for specific goods and services. This study aims to forecast the CPI in Banda Aceh, Indonesia, utilizing CPI data in the region from January 2017 to October 2022 by applying the Fuzzy Time Series Chen and Fuzzy Time Series Markov Chain methods. Forecasting accuracy is assessed by the Mean Absolute Percentage Error (MAPE) and Mean Absolute Error (MAE). The Fuzzy Time Series Chen method obtained a MAPE of 2.98% and an MAE of 3.64, whereas the Fuzzy Time Series Markov Chain method attained a MAPE of 1.07% and an MAE of 1.27. This indicates that the predicting accuracy of the Fuzzy Time Series Markov Chain surpasses that of Chen's Fuzzy Time Series, leading to the conclusion that CPI forecasting in Banda Aceh City utilizing the Fuzzy Time Series Markov Chain approach is more precise.